ANALISIS PENGARUH KOMUNIKASI, BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. IRA WIDYA UTAMA MEDAN - Simbolon, Sahat (Jurnal Manajemen dan Bisnis, 2018)
This study aims to describe the influence of communication, organizational culture and compensation on employee performance at PT. Ira Widya Utama Medan. This research was conducted at PT. Ira Widya Utama Medan which lasted for 3 (three) months, starting from February 2017 until May 2016. This research uses census method. Research respondents are all employees of PT. Ira Widya Utama Medan, amounting to 72 (seventy two) people. The instrument used is a questionnaire to collect data from communication variables, organizational culture and compensation and employee performance variables. Data analysis technique used is validity test, reliability test, descriptive analysis, multicollinearity test, normality test, multiple linear regression analysis, multiple linear correlation coefficient test, partial hypothesis test or t test, simultaneous hypothesis test or F test, and calculation of coefficient of determination. Descriptive analysis results for communication and organizational culture variables are in good category while the compensation and employee performance variables are in the category of good enough PT. Ira Widya Utama Medan. Based on partial analysis, communication, organizational culture and compensation have a positive and significant impact on employee performance at PT. Ira Widya Utama. Based on the simultaneous analysis, communication, organizational culture and compensation have a positive and significant impact on employee performance at PT. Ira Widya Utama Medan. Contribution from communication variable, organizational culture and compensation to improve employee performance variable at PT. Ira Widya Utama Medan is equal to 0.812 or 81.2%, while the remaining 0.188 or 18.8% is influenced by other variables not examined by the authors in this study, suchas leadership, work environment, workmotivation, competence, workcommitment and othesetc